Knowledge, attitude and practice among Health Visitors in the United Kingdom toward children's oral health. Issue 1 (22nd January 2018) - Oge, Ozkem Azmi; Douglas, Gail V. A.; Seymour, Diane; Adams, Cheryll; Csikar, Julia
Abstract: Objectives: The purpose of this study was to determine knowledge, attitude, and practical behavior of health visitors regarding children's oral health in the United Kingdom (UK). Methods: A web‐based self‐administered survey with 18 closed and 2 open ended questions was distributed to a convenience sample of approximately 9, 000 health visitors who were currently employed in the United Kingdom and a member of the Institute of Health Visiting. Results: A total of 1, 088 health visitors completed the survey, resulting in a response rate of 12%. One‐third of the health visitors reported that they had not received oral health training previously. Almost all agreed that oral health advice/promotion should be included in their routine health visiting contacts. Previous oral health training/education was associated with an increase in oral health knowledge; confidence in entering a discussion with parents/caregivers and willingness to be involved in dental referral process. Conclusions: The results of our study support the need for health visitors to receive oral health training in oral health promotion including oral health risk assessment, guidance on evidence based up‐to‐date prevention measures, increasing the dental attendance prevalence at early stages and awareness of including specific oral health guidelines/fact sheets into their regular practice.